Effect of NH3 concentration on the performance of nitrogen doped TiO2 photoelectrochemical cell - Umar A.A.; Rahman M.Y.A.; Saad S.K.M.; Salleh M.M. (2023)
TiO2 nanostructures film synthesized using liquid phase deposition method (LPD) was used as photovoltaic material in photoelectrochemical cell. The anatase phase of TiO2 nanostructures was obtained by annealing the TiO2 samples at a temperature of 400 C before undergoing NH3 treatment with various concentrations, namely, 2.5, 5.0, 7.5, 10.0 and 12.5%. X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), fourier transform infrared (FT-IR) and UV-Vis spectroscopy were performed to characterize the samples. The anatase phase of the TiO2 film was about 240 nm in thickness and 20 nm in diameter with the measured band gap ranging from 2.97 to 3.1 eV for the treated samples. The highest Jsc and power conversion efficiency were 0.76 mA cm-2 and 0.14% obtained from the cell fabricated with 7.5 % NH3. 2012 by ESG.